2018
DOI: 10.7717/peerj.4784
|View full text |Cite
|
Sign up to set email alerts
|

The ΦBT1 large serine recombinase catalyzes DNA integration at pseudo-attBsites in the genusNocardia

Abstract: Plasmid vectors based on bacteriophage integrases are important tools in molecular microbiology for the introduction of foreign DNA, especially into bacterial species where other systems for genetic manipulation are limited. Site specific integrases catalyze recombination between phage and bacterial attachment sites (attP and attB, respectively) and the best studied integrases in the actinomycetes are the serine integrases from the Streptomyces bacteriophages ΦC31 and ΦBT1. As this reaction is unidirectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Mining of the complete N. terpenica AUSMDU00012715 genome (GenBank accession CP046173.1) using antiSMASH v6.0 revealed 49 predicted BGCs, with one BGC showing 59% similarity to the concanamycin BGC. Concanamycin is a polyene macrolide related to the bafilomycins, yet it has an 18-membered macrolactone core (as opposed to the 16-membered core of terpenomycin) and lacks the pentaene side chain of terpenomycin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mining of the complete N. terpenica AUSMDU00012715 genome (GenBank accession CP046173.1) using antiSMASH v6.0 revealed 49 predicted BGCs, with one BGC showing 59% similarity to the concanamycin BGC. Concanamycin is a polyene macrolide related to the bafilomycins, yet it has an 18-membered macrolactone core (as opposed to the 16-membered core of terpenomycin) and lacks the pentaene side chain of terpenomycin.…”
Section: Resultsmentioning
confidence: 99%
“…As we were unable to find any previous studies that had utilized transposon mutagenesis in the genus Nocardia, we looked to systems that had been used in the closely related and better studied Streptomyces. Previous work showed that a codon-optimized hyperactive variant of the transposase Tn 5 could be used to successfully mutagenize Streptomyces species. Due to our previous work adapting Streptomyces genetic elements to function in Nocardia, , Tn5’s preference for high-GC regions of DNA, and similarity in codon usage and GC content between Streptomyces and Nocardia, we hypothesized that this Streptomyces codon-optimized Tn 5 may also function in the Nocardia. Utilizing the vector pHL734, we performed multiple rounds of transformation of N.…”
Section: Resultsmentioning
confidence: 99%
“…Genome sequences for Nocardia terpenica AUSMDU00012715 and Nocardia arthritidis AUSMDU00012717 have been published previously. 41,42 All genomes were analyzed using the AntiSMASH 5.0 Web server (antismash. secondarymetabolites.org).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DNA Extraction. DNA was isolated from N. brasiliensis AUSMDU00024985 according to Herisse et al 41 Transformation Associated Recombination (TAR). TAR capture was performed according to the "Direct Cloning and Heterologous Expression of Biosynthetic Gene Cluster" protocol provided with pCAP03-aac(3)IV (https://media.addgene.org/data/ plasmids/69/69862/69862-attachment_VaRga0ZsUaHw.pdf; see also Tang et al 26 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation